Development of a High-Throughput Screening Assay to Identify Inhibitors of the Major M17-Leucyl Aminopeptidase from Trypanosoma cruzi Using RapidFire Mass Spectrometry. (October 2020) - Izquierdo, Maikel; Lin, De; O'Neill, Sandra; Zoltner, Martin; Webster, Lauren; Hope, Anthony; Gray, David W.; Field, Mark C.; González-Bacerio, Jorge
Leucyl aminopeptidases (LAPs) are involved in multiple cellular functions, which, in the case of infectious diseases, includes participation in the pathogen-host cell interface and pathogenesis. Thus, LAPs are considered good candidate drug targets, and the major M17-LAP from Trypanosoma cruzi (LAPTc) in particular is a promising target for Chagas disease. To exploit LAPTc as a potential target, it is essential to develop potent and selective inhibitors. To achieve this, we report a high-throughput screening method for LAPTc. Two methods were developed and optimized: a Leu-7-amido-4-methylcoumarin–based fluorogenic assay and a RapidFire mass spectrometry (RapidFire MS)–based assay using the LSTVIVR peptide as substrate. Compared with a fluorescence assay, the major advantages of the RapidFire MS assay are a greater signal-to-noise ratio as well as decreased consumption of enzyme. RapidFire MS was validated with the broad-spectrum LAP inhibitors bestatin (IC50 = 0.35 μM) and arphamenine A (IC50 = 15.75 μM). We suggest that RapidFire MS is highly suitable for screening for specific LAPTc inhibitors.